(untitled) (Mustansiria Dental Journal, 2019)
Aim: The aimed study was to evaluate the influence of silver nitrate on surface hardness and tensile strength of acrylic resins. Materials and methods: A total of 60 specimens were made from heat polymerizing resins. Two mechanical tests were utilized (surface hardness and tensile strength) and 4 experimental groups according to the concentration of silver nitrate used. The specimens without the use of silver nitrate were considered as control. For tensile strength, all specimens were subjected to force till fracture. For surface hardness, the specimens were tested via a durometer hardness tester. All specimens data were analyzed via ANOVA and Tukey tests. Results: The addition of silver nitrate to acrylic resins reduced significantly the tensile strength. Statistically, highly significant differences were found among all groups (P≤0.001). Also, the difference between control and experimental groups was highly significant (P≤0.001). For surface hardness, the silver nitrate improved the surface hardness of acrylics. Highly significant differences were statistically observed between control and 900 ppm group (P≤0.001); and among all groups (P≤0.001)with exception that no significant differences between control and 150ppm; and between 150ppm and 900ppm groups(P>0.05). Conclusion: The addition of silver nitrate to acrylics reduced significantly the tensile strength and improved slightly the surface hardness.